Developing Communication and Critical Thinking through Creative Writing in English and French Language: Analysis of Classroom Management Strategies - Irina V. Kulamikhina; Jana Birova; Aleksei Yu. Alipichev; Dinara G. Vasbieva; Olga A. Kalugina (Communications - Scientific letters of the University of Zilina, 2018)
Developing critical thinking skills in university students has become a primary goal in higher education. This study investigated the efficacy of the classroom management strategies for developing critical thinking skills in undergraduate students in the class. The four strategies were incorporated into the 54-hour English program: 1) “Reading circles” strategy; 2) Socratic-questions-based discussions; 3) Group presentations; 4) Writing assignments (abstracts, essays, reports). Students took a multiple-choice pretest and posttest (Cambridge Thinking Skills Assessment Test) and answered a Satisfaction Questionnaire. The study produced several findings: 1) students' overall critical thinking skills made significant improvement by the end of the course; 2) the students showed better academic achievements in English at the end-term exam; 3) the students were more interested and motivated in thinking-based learning; 4) the students found the guided in-class activities (“reading circles”; Socratic-questions-based discussions) more effective than other student-directed activities (group presentations; writing assignments) in developing critical thinking.